THE EFFECT OF OSH PROGRAM AND WORK DISCIPLINE ON THE PERFORMANCE OF FIREFIGHTERS AT THE FIRE SERVICES OF BOGOR DISTRICT IN 2020 - Permatasari, Putri; Wilda Dwi Apriliyani (Journal of Vocational Health Studies, 2021)
Background: Performance is very important in an agency to achieve goals. The implementation of the OSH program and work discipline is one of the important factors to improve employee performance. Purpose: The purpose of this study is to analyze an influence OSH program and work discipline on improving performance in firefighters. Method: This research method is quantitative associative. The sample used was 165 firefighters and rescue workers taken through purposive sampling. Data was collected by filling out a questionnaire. In this study, hypothesis testing will be carried out which includes the F-test (simultaneous test), T-test (partial test), and multiple linear analysis. Result: The results showed that there was a significant effect of the OSH program and work discipline on performance where the value of Fcount = 200.571 > from Ftable = 3.06. The K3 and Work Discipline Program can affect the dependent variable of performance in fire officers at the Bogor Regency Fire Department by 71.2% while the remaining 28.8% is influenced by other variables not included in this study. Conclusion: It can be concluded that there is an influence between the OSH program and work discipline on the performance of firefighters. Therefore, firefighters must always improve their performance to achieve agency goals.